Estudio económicofinanciero de las empresas paleteras de la ciudad de Quevedo y proyección de crecimiento, año 2011. - Vélez Miranda, Yessica Yolanda (2012)
SUMMARY The present investigation was conducted with the aim of improving the lives of small business owners paleteras Quevedo Canton, through feasibility for acquisition of machinery and equipment to enable them to increase production. The Data collection was done through the use of surveys to owners, employees, customers and suppliers paleteras companies, consisting of twenty-six questions, as well as observation and photography techniques. The results obtained showed that 50% of companies have traditional infrastructure and half industrial infrastructure, which we demonstrate that these companies are in the need to purchase new equipment and machinery that minimize time and costs by offering the same quality product. The lack of economic study applied to small businesses paleteras Quevedo Canton, does not disclose its financial performance as a basis to guide them to improve their operations, and therefore the sustained growth of the same, in addition to presenting these shortcomings companies in the management and control of finished products caused by poor planning of an economic study. Were designed and implemented the techniques and methods that once analyzed contributed to the testing of the hypothesis for the respective issue further conclusions and recommendations based on the study developed. The objectives in this study were made to check that the investment project for the acquisition of machinery and equipment dropped a VAN of $2.229,94 and an TIR OF 14% figures alone speak of the viability of the same.